The Victory of Adwa: Religion, Culture, Astronomy, and the Symbolism of the Ark of the Covenant - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2025)
The Battle of Adwa, fought on March 1, 1896, marked Ethiopia’s historic defeat of Italian colonial forces, preserving its sovereignty and inspiring global anti-colonial movements. This victory intertwined religion, culture, astronomy, and the Ark of the Covenant’s symbolism, yet its multifaceted dimensions remain underexplored. This study investigates how these elements—religious motivations, cultural diversity, astronomical timing, and the Ark’s symbolism—shaped Adwa’s success, reinforcing Ethiopia’s national identity and global resonance. A qualitative approach was employed, analyzing archival records, oral histories from Tigrayan and Amhara elders (collected in 2023), and secondary sources. Thematic analysis identified key patterns, triangulated with historical and astronomical data, focusing on the Ethiopian Orthodox Church's role, cultural integration, celestial influences, and symbolic power. The church unified Ethiopia’s diverse populace through faith and the Tabot, while cultural practices and women’s leadership enhanced military effectiveness. Astronomical timing via the Geez calendar suggested strategic alignment, though evidence is inconclusive. The Ark symbolized divine sanction, bolstering identity and inspiring Pan-Africanism. Elders and youth at home supported logistics and morale, ensuring a collective triumph. Adwa’s victory reflects a synergy of religion, culture, and symbolism, underpinned by societal unity, offering a model of resilience against oppression. Future studies should deepen comparative and astronomical analyses, while educational efforts should promote Adwa’s lessons for modern generations.